An effective medium ratio following miniaturized concentric meta‐atom for S‐ and C‐band applications. Issue 6 (30th March 2017) - Hossain, M.J.; Faruque, M.R.I.; Islam, M.T.
ABSTRACT: In this paper, a new effective medium ratio following miniaturized meta‐atom structure designed, fabricated and measured for dual‐band that has multiple circular concentric metal rings printed one inside the other. The each ring of meta‐atom structure delivers a magnetic resonance at different frequencies. The number of concentric ring resonator has created same number of resonances. A different analysis has been performed to verify distinct resonance frequencies, effective medium ratio and electromagnetic transmission properties simply by altering the design parameters. Computer simulation technology (CST) electromagnetic simulator which is commercially available is utilized to investigate the design of the meta‐atom. The dual‐band response has been displayed of the meta‐atom in conjunction with negative index material property over the certain span in the microwave regime. The proposed structure has become suitable for S‐ and C‐band applications and has achieved efficient electrically small microwave structure. © 2017 Wiley Periodicals, Inc. Microwave Opt Technol Lett 59:1233–1240, 2017